https://journal.uokufa.edu.iq/index.php/kje/article/view/15368 - zainab alsaadi; Zoalfokkar Kareem Alobad; Mohammed A. Akraa (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2024)
Epoxy resins are widely used for their strength, chemical resistance, and adhesion, but they are naturally brittle. The objective of this study was to investigate the effects of the addition of a polyurethane (PU) base (polyol) and liquid silicone rubber (LSR (as toughening agents to the epoxy resin. This research focuses on developing a modified flexible epoxy resin by added the toughening agents to epoxy resin was evaluated in various weight ratios (3%, 6%, 9%, and 12%) with (1-methylethyl-1,1'-biphenyl, izoforon diamine) as a hardener. To evaluate the impact of strengthening materials, epoxy samples were tested before and after the addition the toughening agents above. Surprisingly, the mechanical properties exhibited significant improvement according to the results. In case of LSR/Epoxy, (tensile modulus, tensile strength, fracture toughness, and impact strength) were modified at 6wt% LSR. In case of PU/Epoxy, a mechanical property was modified depending on the addition percentage of PU. In conclusion, the 6wt% LSR is the best ratio to modified epoxy. In comparing to PU, each percentage modify a specific property, this difference take place because of the soft elastic flexible nature of PU.